The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1200/jco.2003.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Classification for Hepatocellular Carcinoma: Comparison With Clinical Staging Systems

Abstract: The evaluation of the presence of wild-type or variant ER transcripts in the tumor is the best predictor of survival in patients with HCC. Its accuracy in discriminating patients with good or unfavorable prognosis is significantly greater than that of the commonly used scoring systems for the staging of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 16 publications
3
50
0
1
Order By: Relevance
“…These tumors were responsive to megestrol and unresponsive to anti estrogen tamoxifen. High rates of vERα expression have been shown to be present in men at high risk of HCC development [56,57] . In patients with chronic hepatitis and cirrhosis, the expression of vERα has been associated with higher oxidative stressinduced DNA damage and c-myc mRNA expression, a factor indicating increased genomic instability, augmented cytoproliferation and carcinogenesis [5] .…”
Section: Estrogen Receptormentioning
confidence: 99%
“…These tumors were responsive to megestrol and unresponsive to anti estrogen tamoxifen. High rates of vERα expression have been shown to be present in men at high risk of HCC development [56,57] . In patients with chronic hepatitis and cirrhosis, the expression of vERα has been associated with higher oxidative stressinduced DNA damage and c-myc mRNA expression, a factor indicating increased genomic instability, augmented cytoproliferation and carcinogenesis [5] .…”
Section: Estrogen Receptormentioning
confidence: 99%
“…It is worth noting that a variant form of the wild-type estrogen receptor (wtER) that maintains a constitutive transcriptional activity has been described [22]. Compared with HCCs expressing wtER, HCCs with variant ER (vER) had more aggressive clinical features and insensitivity to tamoxifen [23,24]. In a preliminary, prospective, randomized study of 45 patients with HCC characterized by vER, patients treated with megestrol had a significantly longer median survival time than untreated patients (19 months vs. 7 months; p = .0090) [25].…”
Section: Hormonal Therapymentioning
confidence: 99%
“…As previously reported, ERs, which consist of ERa and ERb, exist not only in female endocrine cells, but also in many types of epithelial cells, including hepatocytes in healthy, cirrhotic, or carcinomatous liver tissue. [14][15][16][17][18][19] ERs in hepatocytes mediate estrogen-responsive biological effects through either DNA binding or in a DNA-independent manner. 20 Regarding nongenomic estrogen signaling, Naugler et al reported, in a murine model, that ERa interferes with interleukin-6 (IL-6)-associated HCC genesis.…”
mentioning
confidence: 99%